Dynamics Modeling and Simulation of Constrained Flexible Load with Manipulator Operation - Liu Qiang; Ge Weimin; Wang Xiaofeng; Zhang Huiyi (Jixie chuandong)
Aiming at the problem that the manipulator operate the flexible load which is constrained by operating environment which the binding force and the load deformation are not easy to control. According to the theory of deformation screw,the dynamics model of the system which manipulator operate the flexible load is established by combining the Lagrangian equation. The system is decomposed into two subsystems: the rigid manipulator and the flexible load. Their dynamics equations are established respectively. According to the constraint relation between the flexible load and the environmental binding force and the end of the manipulator,the motion equation of the system is deduced. In the case of the operating state of a given manipulator and the environmental binding force or the desired trajectory of each joint drive torque and load end of a given manipulator,the inverse kinetics model and the forward dynamics model of the system are deduced. The effectiveness of the proposed method is verified by a 3 DOF manipulator operate a flexible beam.